KESENIAN RANDAI MINANGKABAU DITINJAU DARI SEGI ESTETIKA TARI - Yetti, Elindra (Acintya, 2010)
Randai is an art uniï¬cation of movement, vocal. literature, and theater: Chairul Harun. in Pustaka MsataÂ Budaya qfRandai Minangkabau, describes that Randai has existed through a long historical joumey sine:twentieth century. Randai more develops in the area of Darek. It is an area in central West Sumatera thatbecames a center af Minangkabau culture development. Randai represents a dance of people in gmupÂ moving toforrn a circle, dancing while singing and doing applause and mainly presenting a story. As oneÂ of the dance cultures that becomes an icon afMinangkabau society, this research would like to convey theaesthetic substantion adhered in Randai. The aesthetic aspects that would be studied include the aspects ofÂ harmony, purity and clearance, as well as unity aspect. This article is supposed to give an idea of studyÂ which can complete the aesthetic aspects of Randai as a cultural product.Key wards: Randai, aesthetic, harmony, pure, unity